Training on Household Organic Waste Management Training to Become Organic Fertilizer in Kelurahan Tiakar, Payakumbuh City - Winny Alna Marlina; Devi Yulia Rahmi; Fatma Poni Mardiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
This activity aims to 1) Provide knowledge and training to Tiakar Village, Payakumbuh residents to use recycled waste as valuable compost. 2) Minimize environmental pollution by utilizing waste. Furthermore, 3) provide facilities for the community, especially residents of Tiakar Village, to participate in providing organic waste to be converted into organic fertilizer (compost). The training was carried out at the Tiakar Village Office, Payakumbuh. The training activity was attended by 20 women and fathers from the complex from representatives of each RT/RW in Tiakar Village, East Payakumbuh, West Sumatra. The method for this activity is a lecture method, which transfers knowledge regarding making organic compost fertilizer, discussions and questions and answers with participants, and direct practice in compost fertilizer using an aerobic system. After practice, participants produced 20 kg of compost, each taking home 1 kg. As a result of the activities after the training, compost bags were handed over to the Village Head's Office to collect organic waste around the village. With this program, it is hoped that the training participants will raise awareness to protect the environment and apply the principles of Reuse, Reduce, and Recycle (3R). With this training, participants who attend are expected to act as agents in composting so that organic waste can be used as compost.